POTRET ORGANISASI KEAGAMAAN DAN RESPON TERHADAP DINAMIKA KEHIDUPAN KEBERAGAMAAN DI SALATIGA - Benny Ridwan (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2011)
This research is expected to become contribution for development ofreligious social science. Practically, this research is expected can presentlessons learned for the partys (religious organization), for the agenda ofactivities advocate and empowering of society. This research is focusedat organizational portrait and his religion figure activities. This researchgive information of profile organizations of religion in Salatiga, responseand attitude to dynamics in multicultural society. This research donewith collectively by different researcher, also differ academic backgroundof him. Expected with the difference can enrich viewpoint in analysisand his study.Technique of data collecting done/conducted with interview, observationand data collecting of related/relevant of religious organization,documents, photos, etc. Technique election of responder pursuant tosocial background, education, economic and also the understanding ofreligious experience for them. Responder also come from assumed expertinforman understand with situation, and issue of problem regional. Dataanalysis conducted with descriptive method. Religious organizationalhere cover: Mosque of Al Atiiq, Great Mosque of Darul Amal, JavaneseChristian Church (Gereja Kristen Jawa) Salatiga, Gereja Pantekosta IsaAlmasih Indonesia (GPIAI) Efata Salatiga, The Roman Catholic of ParokiSt. Paulus Miki Salatiga, Parisada Hindu Dharma Indonesia (PHDI),PCNU, PD Muhammadiyah. Interreligious relationship in Salatiga willharmony if role of religion elite can give explanation and calmnesstheologyly and sociological paradigm to the people of each openly andby dialogue. But Interreligious relationship can become underperforming if happened gave economic social, education, and localpolitic management do not in control well.